THE RELATIONSHIP BETWEEN TRAINING INTENSITY, ENERGY AVAILABILITY, AND SLEEP QUALITY WITH THE MENSTRUAL CYCLE OF FEMALE TAEKWONDO ATHLETES - Nurlaila, Syahnaz; Sentani, Muchamad Rizki; Syihab, Syifa F; Insani, Hurry Mega (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Menstrual cycle irregularities are commonly reported by female athletes engaged in physically demanding sports. Menstrual irregularities not only impact athletic performance but also pose potential risks for future health issues such as osteoporosis, infertility, diabetes mellitus, and cardiovascular disease. Factors influencing menstrual cycles include exercise intensity, energy availability, and sleep quality. This study aims to determine the correlation between training intensity, energy availability, and sleep quality with the menstrual cycle regularity among female Taekwondo athletes in the Pelatihan Cabang Taekwondo Indonesia Kabupaten Bandung Barat (PELATCAB TI KBB). This research uses a quantitative approach with a cross-sectional design. The sample consisted of 33 participants selected using total sampling technique. Data were collected through the RPE scale questionnaire, PSQI questionnaire, 2×24 hour food recall, and anthropometric measurements using Bioelectric Impedance Analysis The data obtained were analyzed using the Chi-Square test. The results of the study showed a significant relationship between exercise intensity (p-value = 0.014) and energy availability (p-value = 0.000) with the menstrual cycle. In addition, the study found no significant relationship between sleep quality (p-value = 0.222) and the menstrual cycle of female taekwondo athletes. The conclusion of this study is that training intensity and energy availability have a significant relationship with the menstrual cycle, while sleep quality does not show a significant relationship with the menstrual cycle.